2015
DOI: 10.1159/000377635
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Surgery and Intraocular Pressure

Abstract: Cataract surgery is one of the most performed surgeries in the developed world. In addition to its significant impact on visual acuity, phacoemulsification has been hailed as a potential intraocular pressure (IOP)-lowering procedure. While current evidence suggests an overall significant and sustained decrease in IOP to exist after cataract surgery, the specific ocular characteristics that could help predict which patients are likely to benefit from this IOP-lowering effect remain unclear. This definition is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 48 publications
(57 reference statements)
3
40
1
1
Order By: Relevance
“…Neben der drucksenkenden Wirkung einer Kataraktoperation allein von 1,5-3 mm Hg beim primären Offenwinkelglaukom [9] kann eine Kataraktoperation auch bei wenig eingetrübter Linse im Vorfeld einer Trabekulektomie sinnvoll sein. Nach einer Trabekulektomie kommt es in ca.…”
Section: Braucht Es Die Glaukomchirurgie?unclassified
“…Neben der drucksenkenden Wirkung einer Kataraktoperation allein von 1,5-3 mm Hg beim primären Offenwinkelglaukom [9] kann eine Kataraktoperation auch bei wenig eingetrübter Linse im Vorfeld einer Trabekulektomie sinnvoll sein. Nach einer Trabekulektomie kommt es in ca.…”
Section: Braucht Es Die Glaukomchirurgie?unclassified
“…21,22 Others while corroborating role of lens in etiopathogenesis of glaucoma advise caution in terms of patients who would ultimately gain. 11,17,23 However, a meta-analysis by Freidman et al in 2002 stated that convincing evidence exists for long-term control of IOP only by combined trabeculectomy and cataract operation rather than by cataract operation alone; with average IOP being 3-4mmHg lower in combined group along with need for fewer medications. 24 Advanced surgical trends of current era with enhanced imaging modalities leading to better insight, mandate a more recent update to resolve this dilemma.…”
Section: So the Current Question Is: In The Wake Of Above Findings Camentioning
confidence: 99%
“…Recent literature does document mild glaucoma cases, well controlled on few medications with a visually significant cataract benefit by phacoemulsification and for this subset lens extraction alone may suffice. 23 For those cases with poor control of pressure, IOP reduction after cataract surgery depends on height of pre-op values with a linear correlation irrespective of glaucomatous optic nerve changes. 5,9,15,25 Thus a decision to undertake a lens extraction alone needs to be individually tailored depending on target pressure, patient profile, adherence to medication and accessibility to medical care.…”
Section: A Role In Open Angle Glaucomamentioning
confidence: 99%
“…There was only one trial subject with a diagnosis of primary angle‐closure glaucoma, who was pseudophakic during study enrolment and duration, and exhibited a documented open angle and absence of PAS at study entry. Throughout the short‐study duration, no subjects received any cataract surgery, which has been shown to lower IOP even in eyes with open angles . In addition, no trial participant received any type of laser therapy (peripheral iridotomy/iridoplasty, selective laser trabeculoplasty, posterior capsulotomy) during the study.…”
mentioning
confidence: 99%
“…Throughout the short-study duration, no subjects received any cataract surgery, which has been shown to lower IOP even in eyes with open angles. 3 In addition, no trial participant received any type of laser therapy (peripheral iridotomy/iridoplasty, selective laser trabeculoplasty, posterior capsulotomy) during the study.…”
mentioning
confidence: 99%